ANALISIS KEPATUHAN METODE SCALPING PADA SAHAM SYARIAH TERHADAP FATWA DSN-MUI NO. 80/2011 DAN POJK NO. 15/2015: STUDI KASUS TRADER APLIKASI BIONS BNI SEKURITAS - Fadhil, Rahmatul; Sari, Wilda; Silahuddin, Muhammad (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
Scalping in the Islamic capital market is often considered controversial as it is perceived to involve practices that may contradict Sharia principles. This study aims to analyze the compliance of Sharia stock trading practices using the scalping method by traders at BNI Sekuritas with DSN-MUI Fatwa Number 80 of 2011 and Financial Services Authority Regulation (POJK) Number 15 of 2015. The research employs a qualitative approach through a case study method with a normative juridical framework. Data were collected through focused observations and interviews with stock brokers at BNI Sekuritas, Sharia scalping traders, and DSN-MUI members. The findings indicate that Sharia stock trading practices using the scalping method in the BIONS application of BNI Sekuritas comply with DSN-MUI Fatwa Number 80 of 2011, as no violations of Sharia principles were identified. Additionally, the scalping techniques employed adhere to the provisions of POJK Number 15/POJK.04/2015, as traders strive to avoid practices that conflict with Sharia law. This study confirms that the scalping method can be accepted in the Islamic capital market as long as it adheres to prevailing Sharia principles and regulations.